(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This paper explores the impact of populism on traditional political ideologies, focusing on how populist movements and leaders reshape established political landscapes. Populism, characterized by its appeal to ordinary people against the elite, significantly influences both policy and governance structures, often challenging conventional political norms. The study examines how populism can erode traditional democratic institutions and practices, with populist leaders frequently centralizing power and undermining established checks and balances. This trend is evident in cases such as the rise of Donald Trump in the United States and Viktor Orbán in Hungary, where populist rhetoric has shifted the political discourse and altered institutional dynamics. Additionally, the paper discusses the transformation of economic policies driven by populism. Populist leaders often advocate for protectionist and interventionist measures, diverging from traditional free-market principles. For instance, Trump’s trade policies and Orbán’s economic reforms reflect this shift. The impact on party systems is another critical area of focus. Populism can disrupt traditional party structures, leading to realignments or the emergence of new political actors, as seen with the rise of the Brexit Party in the UK and the Aam Aadmi Party in India. The paper also addresses how populism influences social issues and international relations. By emphasizing identity politics and nationalist agendas, populist movements can reshape public discourse and policy priorities. The impact on international relations is highlighted through examples of isolationist policies and altered global alliances. In conclusion, the study provides a comprehensive analysis of how populism challenges and transforms traditional political ideologies, with implications for democratic governance and political stability.